Development of a simple analytical method for determining trihalomethanes in beer using a headspace solid-phase microextraction technique - Santos,Marcel Silveira dos (2013)
We developed a simple, rapid, and solventless method for analyzing trihalomethanes in beer samples using headspace solid-phase microextraction. The effects of varying experimental parameters, such as extraction temperature and time, addition of sodium chloride, and agitation speed, on extraction yield were studied using a univariate experimental design. Limits of detection between 0.22 and 0.46 µg L- 1 and wide linear ranges were achieved for trihalomethanes. We measured the trihalomethane recoveries and precision (as the standard deviation of repeat measurements) and demonstrated the applicability of the proposed method by analyzing 32 beer samples.